REKONTRUKSI PEMIKIRAN K.H. HASYIM ASY’ARI TENTANG ADAB MURID TERHADAP GURU DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Aditya Ramadhani, Reza; Muqowim, Muqowim (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
The reforms that occurred in the era of the industrial revolution 4.0 have changed various aspects of life, starting from education, economics and social. Even this revolution changed the mindset of student behavior. There are many ethical setbacks that have occurred at this time, especially the problem of student etiquette towards teachers. K.H. Hasyim Asy'ari is a kyai figure who has become a central figurehead thinker in Islamic education. not only a hero who contributes to the needs of the nation. In the book Adabul Alim Wal Mutaallim, he is able to provide an idea that reflects a concept of character education. This concept provides a view of character as a student who is civilized and has an ideal personality, and of course, gives a very positive value for civil society in facing the challenges of the industrial revolution 4.0.